The simulation and implications of thermal plumes produced by Arctic construction in smooth terrain - Outcalt, Samuel I. (Archiv für Meteorologie, Geophysik und Bioklimatologie Serie B, 1972)
In smooth snow covered Arctic terrain human construction produces extreme local variations in the aerodynamic roughness length. These features have been identified on thermal imagery and simulated on a digital computer. The analysis of these features provides a powerful tool for (1) assessing the spatial-temporal integrity of meteorological sites, (2) identifying cultural features in snow covered flat terrain in the relatively low resolution thermal imagery which will be acquired from spacecraft in the next decade, and (3) assessing and attenuating the environmental impact resulting from Arctic construction. Auf glattem, schneebedecktem Terrain der Arktik werden durch Bauten extreme lokale Änderungen in der aerodynamischen Bodenrauhigkeit hervorgerufen. Dieser Effekt konnte sowohl auf Temperaturabbildungen als auch durch numerische Modellrechnungen nachgewiesen werden. Die Analyse dieses Effekts kann dazu verwendet werden, um a) die räumliche und zeitliche Repräsentanz von meteorologischen Stationen zu beurteilen, b) Spuren menschlicher Betätigung in schneebedecktem, ebenem Terrain aus Temperaturabbildungen niedriger Auflösungsgenauigkeit festzustellen, die von zukünftigen Satelliten geliefert werden, und c) den Umweltseinfluß arktischer Bauwerke abzuschätzen. Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/41667/1/704_2005_Article_BF02243186.pdf